Fit and filter integrity of a respirator mask after multiple cycles of autoclave. Issue 3 (24th May 2021) - Desai, Nidhi; Naveed, Hasan; Koenig, Michael; Huber, Jörg; Kapur, Nikil; Bhutta, Mahmood F; Rajak, Saul
Abstract : Background: The COVID-19 pandemic has led to profound shortages in personal protective equipment worldwide. The availability of filtering facepiece class 3 (FFP3) respirators could be greatly increased if they could be reused after sterilisation. Aims: To determine the effects of repeated autoclave cycles on the fit and filter function of the 3M 1863 FFP3 disposable respirator. Methods: Participants underwent fit tests with 3M 1863 FFP3 respirators. Respirators were subjected to autoclave cycles and a repeat fit test was conducted after each cycle until failure. The filter function of both unused and autoclaved respirators was determined by quantitatively assessing the differential pressures and filter penetration of aerosolised sodium chloride particles. Mask structural inspection was also carried out by light microscopy. Results: A total of 38 participants were recruited. Repeat fit testing with a new respirator was passed by 30 of 38 (79%) participants in comparison with 31 of 38 (82%) of participants after the respirator had undergone one autoclave cycle. There was fit test failure with further rounds of autoclave. There was no evidence of structural changes after one autoclave cycle, but the nose foam began to separate from the mask following further cycles. Filter efficiency of all 15 autoclaved respirators that underwent filter testing was 97.40% or more. Differential pressure (breathability) of respirators was unaffected by autoclaving. Conclusions: 3M 1863 FFP3 respirator retains good fit and filter function after a single autoclave cycle. Addressing nose foam separation and further testing to EN149 standards would be required before respirators could be considered for reuse.